Absence of correlation between ABO Rh(D) blood group and neutralizing antibody titers in SARS‐CoV‐2 convalescent plasma donors. Issue 2 (22nd December 2021) - Hirani, Rena; Hoad, Veronica; Gosbell, Iain B.; Irving, David O.
Abstract: Background: Several studies have described associations between ABO blood group and SARS‐CoV‐2 infection severity in hospitalized patients where group A individuals are over‐represented and group O individuals may have a lower infection rate. In convalescent individuals, group B blood donors have higher neutralizing SARS‐CoV‐2 antibody titers. We analyzed whether there was any correlation of ABO Rh(D) blood group with SARS‐CoV‐2 infection and with neutralizing antibodies in Australian convalescent plasma (CP) donors. Study Design and Methods: ABO Rh(D) distribution and demographics of CP donors ( n = 765) were compared with the total blood donor panel ( n = 488, 028), plasmapheresis donors ( n = 203, 176) and whole blood donors ( n = 282, 437) from 2020. The presence of neutralizing antibodies in CP donors was measured using the Vero E6 cell microneutralization assay. Results: The distribution of ABO group in CP donors compared to the total donor panel was not significantly different ( p = .177). There were significantly more group AB donors in the plasmapheresis subset ( p = .005) and group O individuals were over‐represented in the whole blood donor subset ( p < .0001). There was no significant difference in neutralizing antibody levels among CP donors with differing ABO blood groups ( p = .872). Conclusion: ABO Rh(D) blood group distribution was not found to be significantly different between convalescent plasma donors and general blood donors in our large sample group. Inherent blood donor selection biases associated with clinical demand accounted for some differences within CP donors. The levels of SARS‐CoV‐2 neutralizing antibodies were also not significantly associated with ABO Rh(D) group.